Feeding Practices of Children Under-Five in an Industrialized City in Cebu - Sta. Teresa, Marjorie; Rufo, Francis Jemuel; Largo, Geneve (JPAIR Multidisciplinary Research, 2017)
About bout 30% of children under five years old were stunted as a consequence of poor feeding practices and repeated infections. The study determined the feeding practice of mothers of under-five children in Naga City, Cebu, Philippines. The study utilized the descriptive method involving 330 respondents in five districts of the City of Naga, Cebu. Questionnaire was used in data collection and it was translated to Cebuano to extract the necessary data from the respondents. The findings showed the majority of the children under-five year-old were breastfed by their mothers immediately after birth. Furthermore, nearly all respondents did not practice exclusive breastfeeding, however, a considerable number of respondents continue to breastfeed after six months. Plain water, vitamins or medicines and clear broth topped the list of liquids introduced by the respondents, while vitamin A-rich vegetables, foods rich in carbohydrates and iodine-rich foods ranked first, second and third respectively in the list of solid foods for complementary feeding. Most of the respondents did not introduce products that are fortified with iron. Breastfeeding practices in urban areas lack knowledge of the importance of iron-fortified complementary feeding as well as exclusive breastfeeding.